Effects of quercetin on mineralized dental tissues: A scoping review - Nunes, Gabriel Pereira [UNESP]; de Oliveira Alves, Renata [UNESP]; Ragghianti, Matheus Henrique Faccioli [UNESP]; dos Reis-Prado, Alexandre Henrique; de Toledo, Priscila Toninatto Alves [UNESP]; Martins, Tamires Passadori [UNESP]; Vieira, Ana Paula Miranda [UNESP]; Peres, Geórgia Rondó [UNESP]; Duque, Cristiane [UNESP] (My University, 2025)
Objective: This scoping review (SR) aimed to investigate the impact of quercetin on mineralized dental tissues intended to be used in preventive and restorative dentistry. Methods: This SR was conducted following the PRISMA-ScR statement. A comprehensive search was performed across databases for articles published up to March 2024. Eligible studies included in vitro and in situ studies and evaluating the potential therapeutic effects of quercetin on dental enamel and dentin. Data were extracted, and synthesis of study findings was conducted. Results: Out of the 2322 records screened, 22 studies were included in the review. Quercetin, in solution or into dental materials increased the bond strength to enamel and dentin. Additionally, quercetin also enhanced the bond strength of enamel after bleaching. Co-administration of quercetin with fluoride prevented erosive wear and inhibited the proteolytic activity in dentin more effectively than either agent alone. Hardness and modulus of elasticity was higher in dentin treated with quercetin compared to placebo. Reduction of nanoleakage at the composite-dentin interface was reduced in the presence of quercetin as a solution or incorporated into dental adhesives. Conclusions: Quercetin exhibits promising therapeutic effects on mineralized dental tissues, including remineralization and enhancement of bond strength. It shows potential as a multifunctional agent for improving the longevity and effectiveness of dental biomaterials, as well as in preventing erosion and dental caries. However, as these conclusions are largely drawn from lab-based (in vitro) studies, further research, including clinical trials, is needed to fully explore its therapeutic potential and applications in dentistry.
Keywords: Dental caries; Dentin; Enamel; Polyphenols; Tooth erosion